Differential response of pea (Pisum sativum) genotypes exposed to salinity in relation to physiological and biochemical attributes - SANWAL, S K; KUMAR, ASHWANI; MANN, ANITA; KAUR, GURPREET (The Indian Journal of Agricultural Sciences, 2023)
Pea (Pisum sativum L.) is moderately tolerant to salinity, early vegetative stage being more sensitive to salinity. In view of this, twenty pea genotypes collected from IIVR, Varanasi were screened for salt tolerance in terms of physiological and biochemical traits. The experiment was conducted in randomized complete block design in pots filled with soil (EC 20.47 dS/m) in 3 replications. Osmotic stress was created with irrigation water of salinity ECiw6 and 9 dS m-1 alongwith best available water (BAW) having ECiw 0.6 dS m-1 (control). It was found that mean photosynthetic rate (Pn)decreased with increasing levels of salinity in all the genotypes except VRPMR-11 (12.6%), VRP-5 (16.18%) and VRP-22 (16.5%) at ECiw9 dSm-1.The chlorophyll content was also significantly higher in VRPE-25, VRP-5 and VRPE-100 over all the treatments. Fv/Fm values reduced by 12.9% at ECiw6 dSm-1 and 24.19% at ECiw9 dSm-1. The best indicator of stress, proline accumulated many folds with increasing levels of salinity, i.e. approximately 8 folds proline content at ECiw6 dSm-1 and 13 folds proline content at ECiw9 dSm-1 was observed. The membrane damage in terms of lipid peroxidation was measured as MDA content and accumulated significantly at higher saline level followed by ECiw 6 dSm-1 and least in control. Leaf K+/Na+ ratio decreased significantly with increasing stress level. Among the genotypes, significantly higher K+/Na+ was observed in VRP-22, whereas minimum in VRP-343 and VRPE-25. More than 80 % reduction in yield was observed in pea genotypes VRP-6, VRPE-100, BB-29(b)-14 green, VRP-233, PC-531, VRP-12-1 and VRP-7, whereas the minimum reduction was obtained in VRPE-101 (39.1%), VRP-343 (43.2%), Pusa Pragati (43.8%), VRP-22 (45.8%), and VRPE-25 (48.37%) at ECiw9 dS m-1. Thus on the basis of the physiological and biochemical expressions of tolerance, these genotypes were characterized as sensitive, moderately tolerant or tolerant to salinity.